Recovery trends and correlation of non invasively isolated mammary epithelial cells with milk yield in Surti and Mehsani buffaloes during early lactation - Tyagi, Kuldeep Kumar; Brahmkshtri, Balkrushna Pratapchand; Kharadi, Vishnubhai Bhikabhai; Ramani, Umed Vitthalbhai; Pandya, Gaurav Mulvant; Janmeda, Mamta (Buffalo Bulletin, 2021)
This study aims to elucidate recovery trends and correlation of non-invasively isolated mammary epithelial cells with milk yield in Surti and Mehsani buffalo breeds during early lactation. Surti and Mehsani buffaloes, 13 each maintained at Livestock Research Station, Navsari and Sardarkrushinagar, Dantiwada, Gujarat, India respectively were selected for the study. Milk samples were collected repeatedly from the same buffaloes at 15th and 60th day postpartum (pp). Buffaloes were categorized for data analysis and comparisons in to four groups viz. S15 (Surti buffaloes 15th day pp), S60 (Surti buffaloes 60th day pp), M15 (Mehsani buffaloes 15th day pp) and M60 (Mehsani buffaloes 60th day pp). The total somatic cells were separated from milk samples through centrifugation and primary bovine mammary epithelial cells (pBMEC) were obtained from total somatic cells using antibody mediated magnetic separation method. There was significant decrease in mean somatic cell count (SCC) with advancement of lactation to the tune of 18.72% in Surti and 16.84% in Mehsani buffaloes from day 15 to 60 pp. Comparable recovery of pBMEC (2.13 to 3.45%) from total somatic cells was observed over the advancement of lactation and between breeds. The pBMEC and SCC had exhibited negligible to low and non significant correlations with cumulative milk yield (CMY) and Test day milk yield (TDMY). Thus, it can be concluded that pBMEC can successfully be recovered from somatic cells. pBMEC and SCC both does not proved to be a significant explanatory variable for milk yield in buffalo breeds under study.